The Persistent Effects of Short-Term Peer Groups in Higher Education - Petra Thiemann (Institute of Labor Economics (IZA), 2017)
This paper demonstrates that short-term peer exposure can generate achievement effects which persist for several months and years. I study a mandatory freshmen week for first-year undergraduates and exploit the random assignment of students to freshmen teams. I find that the freshmen week contributes to the formation of persistent social ties. Furthermore, peers' observable characteristics impact college achievement for up to three years. Ability peer effects are non-linear, i.e. very high or low levels of average peer ability in a group harm students' grades. These effects are most pronounced for low-ability students.
Keywords: I21; I23; J24; 330; peer effects; higher education; natural experiment; gender; region of origin; ability